Comprehensive assessment of elite forms of black currant of the Ural selection for suitability to mechanized harvesting - E. М. Chebotok (Аграрная наука Евро-Северо-Востока, 2024)
In the conditions of the Sverdlovsk region (Middle Urals), a comprehensive assessment of elite forms of black currant was carried out to identify those suitable for mechanized harvesting with intensive cultivation technologies. The objects of research were 12 elite forms of black currant bred by the Sverdlovsk Breeding Station of Horticulture (planting 2018, layout 3×1 m). The research was carried out in 2021–2023 according to generally accepted methods. The studies were carried out according to generally accepted methods. According to the height of the bush, elite forms 3-2-05-08, 3-8-05-08, 5-2-05-08, 2-11-05-08 were distinguished – the measurement result was 100...110 cm; by the width of the bush – 3-1-05-08, 3-5-05-08, 3-8-05-08, 5-2-05-08 – 110...120 cm. The diameter of the base of the bush for most variety samples was 20.. 30 cm. The number of bent branches in all forms was less than 5 %, the diameter of the branches 8...15 mm. The average weight of berries was 1.5 1.8 g for elite forms 2-11-05-08, 3-5-05-08, 4-6-05-08, 4-7-05-08, 5-2 -05-08. The crushing force of berries in the studied variety samples was 201...367 g. Based on the force of berry separation, elite forms 3-5-05-08, 4-5-05-08, 5-4-05-08 stood out – 50 57 g. According to the results of the assessment of suitability for mechanized harvesting, the elite form of black currant 3-5-05-08 has optimal values in all parameters. Elite forms 2-11-05-08, 3-1-05-08, 3-8-05-08, 5-2-05-08, 4-6-05-08, 4-7-05-08, 5-4-05-08 are subjected to testing under production conditions. The following variety samples are not suitable for mechanized harvesting: 3-4-05-08, 4-5-05-08, 5-1-05-08, 5-3-05-08. In the conditions of 2023, elite forms 4-5-05-08, 5-1-05-08 were characterized by resistance to fungal diseases.